Mine Road Design Feasibility and Its Impact on Overburden Hauling Productivity at PT PBT - Mutia Septriandini; Aleksander Purba; Rahayu Sulistyorini (RESWARA: Jurnal Riset Ilmu Teknik, 2026)
This study aims to analyze the feasibility of overburden (OB) hauling road design on production productivity and operational efficiency at PT PBT. The research employed a quantitative descriptive method through several stages, including preparation, data collection, data processing, data analysis, and conclusion formulation. Primary data were obtained through measurements of hauling road geometric parameters, including road width, grade, cross slope, superelevation, turning radius, cycle time, hauling equipment productivity, and fuel consumption. The results indicate that most road geometric parameters did not comply with technical standards, where the actual road width ranged from 17,1-19,1 m and the road grade reached 9%. These conditions increased operational resistance and hauling equipment cycle time. After the hauling road redesign was implemented, hauling equipment productivity increased from 108.34 BCM/hour to 130.69 BCM/hour, representing an improvement of 20.63%, while cycle time decreased from 13.45 minutes to 11.15 minutes. In addition, fuel consumption decreased by 10.21%, from 441.88 liters/hour to 396.74 liters/hour, resulting in significant operational cost savings. Therefore, improvements in hauling road geometry were proven to enhance mining productivity and operational efficiency.